Pubertal maturation and health risk behaviors in adolescents: a systematic review - Azevedo, Kesley Pablo Morais de (2017)
Background: The objective of this study is to accomplish a systematic review of the literature describing the associationbetween pubertal maturation and health risk behaviors among adolescents. Methods: It was used the database from MEDLINE/Pubmed, Scopus, Lilacs and Web of Science. The terms used in the research, with its variations, were “puberty”, “maturation”, “maturity”, “risk behaviors”, “risk factors”,“adolescent” and “student”. There were included studies that considered: 1) pre-teens and teenagers aged from 10 to 19 years old; 2) have at least one aspect in regards to pubertal maturation, and at least one behavior of risk (or the data that shows prevalence); 3) observational, transversal and longitudinal studies, and evaluate an association between pubertal maturation and behaviors of risk; 4) be published in scientific journals in the English language; and 5) be published until July, 2015. The quality of the scientific papers was assessed based on the Downs & Black scale. Results: Out of 838 manuscripts found in the databases, after the sorting and applied the eligibility criteria, remained in this systematic review 13 articles. Early maturation was associated significantly with the use of alcohol, cigarettes and illegal drugs, early sexual initiation, sedentary behaviors and involvement in fights, where girls showed higher prevalence. Conclusion: The results of the current study indicates that a pubertal maturation is associated to health risk behaviors among adolescents.